2019
DOI: 10.1038/s41598-019-45890-w
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal synergy of a topical triazole, PC945, with a systemic triazole against respiratory Aspergillus fumigatus infection

Abstract: Invasive pulmonary Aspergillosis is a leading cause of morbidity and mortality in immunosuppressed patients and treatment outcomes using oral antifungal triazoles remain suboptimal. Here we show that combining topical treatment using PC945, a novel inhaled triazole, with systemic treatment using known triazoles demonstrated synergistic antifungal effects against Aspergillus fumigatus (AF) in an in vitro human alveolus bilayer model and in the lungs of neutropenic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…Preclinical studies show synergy between topical PC945 and systemic voriconazole or posaconazole. 101 Clinical trials are ongoing in allergic asthma in patients infected by Aspergillus and Candida, in cystic fibrosis patients infected by Aspergillus, and for the early treatment of Aspergillus infections in lung transplant patients (https://clinicaltrials.gov). • Olorofim (F901318) is an inhibitor of dihydroorotate dehydrogenase.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies show synergy between topical PC945 and systemic voriconazole or posaconazole. 101 Clinical trials are ongoing in allergic asthma in patients infected by Aspergillus and Candida, in cystic fibrosis patients infected by Aspergillus, and for the early treatment of Aspergillus infections in lung transplant patients (https://clinicaltrials.gov). • Olorofim (F901318) is an inhibitor of dihydroorotate dehydrogenase.…”
Section: Discussionmentioning
confidence: 99%
“…Since we believed that inhaled treatment with PC945 would be likely to be combined with systemic treatment with another antifungal agent when used to treat invasive disease, the effects of combination therapy versus monotherapy were investigated. We found that combining topical treatment using PC945, with systemic treatment using known triazoles, demonstrated superior antifungal effects against A. fumigatus in an in vitro human alveolus bilayer model and in the lungs of neutropenic immunocompromised mice than systemic triazole alone [ 52 ].…”
Section: Pc945: Preclinical Profilementioning
confidence: 99%
“…Using a method from the European Committee on Antimicrobial Susceptibility Testing (EUCAST), against 96 clinically isolated A. fumigatus strains obtained in France and the United Kingdom, geometric mean minimum inhibitory concentration (MIC) of PC945 was 0.17 μg/mL, and MIC 50 and MIC 90 values were 0.125 and 1.0 μg/mL, respectively; the potency of PC945 was superior to that of voriconazole and comparable to that of posaconazole 13 . PC945 was also found to inhibit A. fumigatus infection in an in vitro human alveolus bilayer model 14 . In animal models, PC945 delivered a sustained and persistent antifungal effect in the lung when administered intranasally 15 .…”
Section: Introductionmentioning
confidence: 99%
“…13 PC945 was also found to inhibit A. fumigatus infection in an in vitro human alveolus bilayer model. 14 In animal models, PC945 delivered a sustained and persistent antifungal effect in the lung when administered intranasally. 15 In addition, PC945 was more effective than alternative antifungal agents because of a higher local exposure at the infected site, which was attributed to the intranasal administration delivering the compound directly to the lung.…”
Section: Introductionmentioning
confidence: 99%